Strengthening Arabic Language Skills: Effective Learning Strategies for Students in Dormitories - khotimah, Siti Khusnul; Ilmiani, Aulia Mustika (Uktub: Journal of Arabic Studies, 2024)
This study aims to identify effective learning strategies used in Arabic language learning for university students in IAIN Palangka Raya dormitories. Qualitative research methodology was applied through in-depth interviews, participatory observation, and documentation analysis. The results show that the use of communication-based learning strategies, the creation of an Arabic-speaking environment, task-based approaches, and intensive guidance and mentoring are very effective in improving students' Arabic language skills. Students who communicate in Arabic on a daily basis show a significant increase in speaking ability. An environment filled with Arabic language elements supports continuous learning, while task-based approaches and contextualized learning increase student engagement and motivation. Technology provides additional flexible resources, and extracurricular activities and collaboration between students build a supportive learning community. The combination of these various strategies creates a comprehensive and effective learning approach, which can be applied in other educational institutions to improve Arabic language acquisition. This research fills a gap in the literature by providing specific insights into effective learning strategies in a boarding school context, offering practical guidelines for other educational institutions.